Silver Nanoparticles in Biomedical Applications: Insights from In Vitro and In Vivo Studies - Mahajan Shriya; Soni Ishika; Sharma Nidhi; Singla Tara; Saxena Anil Kumar; Sateesh N.; Jetly Mahesh; Hussain Laeth (E3S Web of Conferences)
This work provides a thorough examination of the biological impacts of silver nanoparticles (AgNPs) via in vitro and in vivo investigations. In vitro tests demonstrated a concentration- dependent reduction in cell viability, decreasing from 90% at 5 µg/mL to 50% at 25 µg/mL, with a substantial rise in reactive oxygen species (ROS) from 20% to 80%. The data indicate that AgNPs may possess cytotoxic effects. Moreover, apoptosis rates escalated from 5% to 18% with increasing doses of AgNP. In vivo investigations revealed significant alterations in hematological parameters, including a decrease in hemoglobin concentrations (from 15 g/dL to 11 g/dL), an elevation in white blood cell counts (from 8 x10³/µL to 12 x10³/µL), and a drop in platelet counts (from 250 x10³/µL to 200 x10³/µL) corresponding to escalating AgNP dosages. Histological studies demonstrated dose-dependent changes in organ tissues, especially the liver, with scores escalating from two to six. Tumor size reductions of 20%, 40%, and 60% were seen with low, medium, and high dosages of AgNPs, respectively. These results underscore the promise of AgNPs for biological applications, especially in tumor therapy. Nonetheless, comprehensive safety evaluations and accurate dosage optimization are required prior to their clinical use. This work highlights the potential biological uses of AgNPs while stressing the need of meticulous evaluation to guarantee their safe and effective incorporation into medical procedures.